Екшн сцени у кінематографі та мультиплікації – основні принципи побудови сцени - Кондратенко, Є. М. (ХНУРЕ, 2024)
This work is a comparison of ways to show action scenes using animation methods and cinematography methods. Animation – is a prolongation of draw ing as a method to show the audience information. With the rise of computer technologies animation upgrades its technics but it leaves basic principles. Same goes for the cinematography. Even after upgrading the filming equipment and post-production services, basic principles stay the same. This work compares animated action scenes with ones from films and TV-series, breaking down key differences in frames and approaches producers use.
Keywords: мультиплікація; кінематограф